Virulence gene and antibiogram profile as markers of pathogenic Escherichia coli in tropical beaches of North Western India: Implications for water quality and human health. (31st August 2018) - Maloo, Aayushi; Fulke, Abhay B.; Khade, Komal; Sharma, Awkash; Sukumaran, Soniya
Abstract: The purpose of the present study was to investigate the presence of pathogenic Escherichia coli in anthropogenically marred tropical beaches of Mumbai, India. Out of 200 presumptive E. coli, (n = 125) isolates were analysed for presence of virulence genes specific to diarrheagenic pathotypes using a molecular approach. Fifty four percent of the isolates screened possessed at least one virulence gene. The presence of stx1, stx2, eaeA and hlyA genes was detected in 9%, 13%, 20% and 8% of isolates respectively, LT1 and ST1 genes was detected in 9% and 11% of isolates respectively. Also, Versova had higher prevalence of EPEC pathotype, Juhu and Girgaon had higher prevalence of EHEC and ETEC pathotypes, Dadar and Mahim had higher prevalence of ETEC pathotype. 100% of the isolates were Multiple Antibiotic Resistant with higher MAR indices stipulating an important human health concern due to a risk of developing water borne disease associated with exposure to contaminated waters. Graphical abstract: Image 1 Highlights: Coastal waters of selected Mumbai beaches were found to be contaminated with fecal matter confirmed by detection of heavy loads of Escherichia coli. Presence of virulence genes specific to EHEC, EPEC, ETEC and STEC pathotypes in E. coli indicated health risk to public exposed to contaminated water during recreational activities. Higher Antibiotic resistance indices indicated high risk source of contamination. Effective measures (e.g. Proper sanitation, efficient disposal facility and wastewater treatment) should be undertaken.